TEMPORAL DYNAMICS OF PLANKTON COMMUNITIES IN AN ABANDONED ENVIRONMENT: A COMPREHENSIVE POND STUDY - NASEER , BUSHRA; SINHA, SHAILENDRA KUMAR (The Bioscan, 2023)
In a year-long study of an abandoned Pond Rejali (PR) in Dhanbad, Jharkhand, plankton community study was carried out in order to find out the current ecological condition of the pond and its possible utilisation. Among the abiotic factors, variation in temperature (16-36 °C), transparency (15-19.5 cm), dissolved oxygen (1.5-8.6 mg/ L), total dissolved solids (970-1250 mg/L), nitrate concentrations (0.10-0.19 mg/L), phosphate levels (0.43-1.05 mg/L), chloride content (14-65 mg/L), BOD (4.6-8 mg/L), and COD (36-76 mg/L) have been recorded. Diversity indices revealed moderately to highly diverse zooplankton communities (Shannon Diversity Index as 3.04 and Simpson’s Diversity Index value as 0.95). Phytoplankton showed slightly lower diversity (Shannon Diversity Index value as 2.22).